ANALYSIS OF INTERNAL CONTROL OF INVENTORY ACCOUNTING INFORMATION SYSTEM AT PT. ANDRE LAURENT - Muchamad Aqil Nugroho (Dinasti International Journal of Education Management And Social Science, 2019)
Accounting information system (AIS) is used to assist data processing in a company with the aim to optimize the performance of employees based on the duties and responsibilities of each employee. PT Andre Laurent currently still has obstacles in recording its inventory that causing the difference of inventory stock. This study aims to analyze the procedures of accounting information systems and implementation of internal controls in the company and to design proposals and also to implement a good accounting information system for the company. The research method used in this research is qualitative research method, data collection method by interview, observation or direct observation to the company, documentation and questionnaire is distributed to users of accounting information system proposed based on the discussion. The results of the research are such as the application of FIFO (First-In First-Out) method to inventory recording, improvement of procurement and expenditure procedures, and implementation of Accurate 5 Education Software that will optimize the company's operational activities.